Controlled apneic tracheostomy in patients with coronavirus disease 2019 (COVID-19)Central MessagePerspective - Kathleen D. Weiss, MD; Antonio Coppolino, III, MD; Daniel C. Wiener, MD; Ciaran McNamee, MD; Robert Riviello, MD; Ju-Mei Ng, MD; Michael T. Jaklitsch, MD; Margaret B. Marshall, MD; Matthew M. Rochefort, MD (JTCVS Techniques)
Objective: To develop a team-based institutional infrastructure for navigating management of a novel disease, to determine a safe and effective approach for performing tracheostomies in patients with COVID-19 respiratory failure, and to review outcomes of patients and health care personnel following implementation of this approach. Methods: An interdisciplinary Task Force was constructed to develop innovative strategies for management of a novel disease. A single-institution, prospective, nonrandomized cohort study was then conducted on patients with coronavirus disease 2019 (COVID-19) respiratory failure who underwent tracheostomy using an induced bedside apneic technique at a tertiary care academic institution between April 27, 2020, and June 30, 2020. Results: In total, 28 patients underwent tracheostomy with induced apnea. The median lowest procedural oxygen saturation was 95%. The median number of ventilated days following tracheostomy was 11. There were 3 mortalities (11%) due to sepsis and multiorgan failure; of 25 surviving patients, 100% were successfully discharged from the hospital and 76% are decannulated, with a median time of 26 days from tracheostomy to decannulation (range 12-57). There was no symptomatic disease transmission to health care personnel on the COVID-19 Tracheostomy Team. Conclusions: Patients with respiratory failure from COVID-19 disease may benefit from tracheostomy. This can be completed effectively and safely without viral transmission to health care personnel. Performing tracheostomies earlier in the course of disease may expedite patient recovery and improve intensive care unit resource use. The creation of a collaborative Task Force is an effective strategic approach for management of novel disease.